Immobilization of tobacco etch virus (TEV) protease on a high surface area protein nanofibril scaffold. (8th September 2018) - Raynes, Jared K.; Domigan, Laura J.; Pearce, F. Grant; Gerrard, Juliet A.
Abstract : Tobacco etch virus (TEV) protease is widely used for the removal of poly‐histidine affinity tags from proteins. In solution, it is a one‐time use enzyme for tag cleavage that has low stability, and is therefore a good candidate for immobilization. Amyloid fibrils can act as a versatile nanoscaffold by providing a large surface area for biomolecule immobilization. Immobilization of TEV protease to amyloid fibrils grown from the surface of a small glass bead, using physisorption, successfully immobilized active TEV protease. The bead retained activity over several uses and successfully cleaved a poly‐histidine tag from several his‐tagged proteins. This is first time that TEV protease has been immobilized to insulin amyloid fibrils, or any protein based support. Such functionalized surface assembled amyloid fibrils show promise as a novel nanosupport for the creation of functional bionanomaterials, for example, active surface coatings for the production of fine chemicals, chemical detoxification, or biosensing. Insulin amyloid fibrils provide a new nanosupport for the immobilization of TEV protease, which could allow for the reuse of the enzyme, saving on production costs for recombinantly expressed poly‐histidine tagged proteins. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 34:1506–1512, 2018